Enhanced exon skipping and prolonged dystrophin restoration achieved by TfR1-targeted delivery of antisense oligonucleotide using FORCE conjugation in mdx mice. Issue 20 (10th August 2022) - Desjardins, Cody A; Yao, Monica; Hall, John; O'Donnell, Emma; Venkatesan, Reshmii; Spring, Sean; Wen, Aiyun; Hsia, Nelson; Shen, Peiyi; Russo, Ryan; Lan, Bo; Picariello, Tyler; et al.
Abstract: Current therapies for Duchenne muscular dystrophy (DMD) use phosphorodiamidate morpholino oligomers (PMO) to induce exon skipping in the dystrophin pre-mRNA, enabling the translation of a shortened but functional dystrophin protein. This strategy has been hampered by insufficient delivery of PMO to cardiac and skeletal muscle. To overcome these limitations, we developed the FORCE TM platform consisting of an antigen-binding fragment, which binds the transferrin receptor 1, conjugated to an oligonucleotide. We demonstrate that a single dose of the mouse-specific FORCE–M23D conjugate enhances muscle delivery of exon skipping PMO (M23D) in mdx mice, achieving dose-dependent and robust exon skipping and durable dystrophin restoration. FORCE–M23D-induced dystrophin expression reached peaks of 51%, 72%, 62%, 90% and 77%, of wild-type levels in quadriceps, tibialis anterior, gastrocnemius, diaphragm, and heart, respectively, with a single 30 mg/kg PMO-equivalent dose. The shortened dystrophin localized to the sarcolemma, indicating expression of a functional protein. Conversely, a single 30 mg/kg dose of unconjugated M23D displayed poor muscle delivery resulting in marginal levels of exon skipping and dystrophin expression. Importantly, FORCE–M23D treatment resulted in improved functional outcomes compared with administration of unconjugated M23D. Our results suggest that FORCE conjugates are a potentially effective approach for the treatment of DMD. Lay Summary: The biggest problem confronting oligonucleotide therapeutics is a lack of compounds capable of targeting compounds to diseased tissues. This paper reports a major advance targeting the transferrin receptor to increase the delivery of morpholine oligomers to muscle cells in vivo. This work suggests the possibility for improved treatments of muscular dystrophy and other diseases. Graphical Abstract: